A cultura de segurança na perspectiva da equipe multiprofissional de saúde que atua em unidades de terapia intensiva adulto em hospitais de grande porte do município de Belo Horizonte - Bárbara Pequeno Andrade Rasslan Silva (2021)
Measuring the safety culture through validated instruments allows the knowledge of factors relevant to patient safety in the institution’s routine and in employees’ behavior, thus enabling the discovery of strengths that must be encouraged and weaknesses that must be restructured. Methodology: this is a cross-sectional descriptive study with a quantitative approach, survey type. The questionnaire “Hospital Survey on Patient Safety Culture” was used as a data collection instrument. The sample consisted of 168 health professionals who worked in the adult intensive care area of four hospitals in Belo Horizonte. For data analysis, absolute and relative frequencies of positive/neutral and negative responses for each dimension were measured. In addition, a factor analysis was performed, which generated 12 indicators that represented the 12 dimensions of the instrument. To check the convergent validity the Average Variance Extracted – AVE criterion was used and to measure the reliability of the instrument, Cronbach’s Alpha (C.A.) and Composite Reliability (C.R) were used. Results: the multidisciplinary team was mostly composed of female nursing technicians, with an average age of 39.97, an average weekly workload of 35.07 hours. Only the dimension “Organization learning/Continuous improvement” was classified as strong in the perspective of the four organizations. On the other hand, the dimension that obtained the lowest percentage of positive responses in the evaluation of the four hospitals was “Non-punitive responses to errors”. Hospital A had the highest number of dimensions classified as weak (nine) and Hospital D had the lowest number of dimensions classified as weak (one). Conclusion: Of the 12 dimensions analyzed, one was classified as strong and six were classified as weak. In addition, in the multivariate analysis, Hospital D presented a positive evaluation in relation to the other institutions in ten of the twelve indicators analyzed. The study showed that the punitive culture still prevails in the health environment and that it is essential to develop tools and studies that strengthen the safety culture within intensive care.